AL-IZDIWAJIYYAH AL-LUGHOWIYAH FII ISTIHDHAMI AL-LUGHOH AL-‘ARABIYAH - Muslimin, Imam (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2010)
Al-Izdiwajiyyah (diglosia) is standardizing a specific language when there are two variants of language that live side by side in societal life and each variant has its own social function. Disglosia is related to the use of local languages variations of low language and high language in a community. In Arabic language, disglosia covers dialects among the speakers, for instance there are two variants of language that each has roles and functions. The use of the variant depends on the situation. The most important characteristic of diglosia is specifying the functions of wach language variant. For high level language variant is aimed for formal situations such as religious ceremony, lectures, news, or editorials of newspaper. On the contrary, the low level language variant is commonly used in less formal situation such as daily communication in the family, chat with friends, stories in radion, and folk literature. In Arabic language, diglosia can be identified when the speaker of the language use diction commonly used for daily communication (amiyah) in a formal expression (fusha), and vice versa.